Independent and effective adjudication in the lower courts of South Africa - Rawheath, Pawranavilla (Department of Public Law, 2023)
Most dispute resolution in South Africa takes place in the lower courts, mainly the Magistrates' Courts (MCs), and they therefore constitute the foundation upon which the country's administration of justice rests. Indeed, since the establishment of a constitutional democracy in South Africa and the declaration of MCs as independent, the lower courts constitute the largest component of the judiciary and the institution where most people seek the protection of the rule of law. Although the critical importance of the work of MCs in communities is common knowledge, very little attention has been given to the subject of lower court dispute resolution in the jurisprudence and the scholarly literature. Under the circumstances, the discourse about judicial independence and courts' effectiveness is situated in a judicial system in which MCs do not feature. Several related explanations may be given for the absence of lower courts from these debates, not least of which is the pre – constitutional historical location of MCs within the executive of a state where an illegitimate Parliament was sovereign. Yet, given the rather obvious present importance of the lower courts in the judicial system, there is a need to draw them to the centre of the debate. This shift is especially important considering the enormous challenges which confront lower courts to effectively adjudicate disputes in high volumes and varied in nature and complexity. When the work of MCs is raised in discussions about the judiciary, commentary is invariably negative in tone especially with reference to the poor quality of judicial decisions and the inefficiency that plagues the judicial system at lower court level. Criticisms of this kind are not unjustifiable but serve little purpose unless they lead to the identification of the root causes, the ways to resolve them and importantly, appropriate remedial action by the responsible institutions. The transformational vision of the Constitution calls for all state organs to support the courts to adjudicate the vast and varied disputes, claims and charges impartially, independently and effectively. However, the veritable invisibility of the issues and challenges that confront MCs in the prevailing discourse may have enabled the responsible entities to neglect it. As a consequence, MCs have continued to function as they did in the pre – constitutional era: still mainly under the governance and management of the executive and in a position of inferiority. As the notion of impartiality and the characterisation of all courts as independent are central to dispute resolution, the issues arising from the debates constitute the core subject matter this thesis traverses. This thesis posits the view that the prolonged, degraded status of lower courts may continue to weaken the public confidence in these courts and may imperil the legitimacy of the judiciary as a whole in the long term.